Studi Foundational Problem Pendidikan: Sosiologis, Budaya Sebagai Pengembangan Kurikulum - Lutfi, Muhammad Khoirul (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
Sociology's attention to educational activities is increasingly intensive. This presupposes the creation of harmonious and peaceful social life, as well as the creation of values, norms, and social systems that bind social life and must be obeyed by each member of society. The sociological foundation of education in Indonesia adheres to an integralistic ideology that originates from the norms of social life: (1) kinship and cooperation, togetherness, deliberation for consensus, (2) mutual prosperity is the goal of social life, (3) the state protects its citizens, and (4) harmonious balance between rights and obligations. Therefore, education in Indonesia not only improves the human quality of individuals but also the quality of the structure of society. The four areas studied are essential as suggestions for understanding the education system about the whole life of society. Furthermore, as we all know, the development of science and technology is very rapid, and the rate of development is so broad that it almost covers all aspects of human life. Especially in the field of information and communication, this is the background for the need to apply science and technology in the field of educational curriculum development.